DIURETICS EFFECT OF AVOCADO LEAF (Persea americana Mill.) ETHANOL EXTRACT ON THE GASTRIC HISTOLOGY OF WISTAR MALE RATS (Rattus norvegicus) - Dwi Erlinda; Mahriani Mahriani; Susantin Fajariyah (Universitas Medan Area, 2020)
Irregular urine output triggers kidney stone disease. One way to cure it is by using synthetic diuretic compounds. The use of synthetic diuretic drugs for a long time can cause side effects, namely gastric damage. Therefore, research is needed to determine the diuretic effect of ethanol extract of avocado leaves (Persea americana) and its effect on the histological structure of the gastric of male rats. Avocado leaf extract is made by maceration method, using 70% ethanol and then evaporated. Wistar male rats were divided into 5 treatment groups namely negative control (aquadest), positive control (furosemide), avocado leaf extract dose of 50 mg / kg body weight, 100 mg / kg body weight, and 150 mg / kg body weight with oral administration for 15 days. The volume of urine was measured for 24 hours, then the mice were sacrified on the 16th day. Gastric organs were taken for histological observation by the paraffin method and Hematoxylin and Eosin (H&E) staining. The results showed that the optimum avocado leaf ethanol extract was a dose of 100 mg/kg showed a diuretic effect but did not affect the histological structure of the gastric.